A Contribution to Studying the Effect of Wind Loads on RC Tall Buildings Using Performance-Based Analysis (Framed Systems) - ناصر أحمد; غاندي جحجاح; بسـام حويجـة (Latakia University Journal -Engineering Sciences Series, 2024)
This paper aims to evaluate the inelastic behavior of tall concrete buildings exposed to wind loads, and to compare the performance objectives with the limits of acceptance standards available in international codes, using nonlinear static analysis. Two models were studied: the first model (A) consists of 14 floors, while the second model (B) consists of 10 floors. The structural systems of the selected models is a group of reinforced concrete frames, designed according to the Syrian Arab Code, to evaluate the nonlinear structural response under the influence of Wind loads. The modeling was done using ETABS 2018 software where 3D models were created, which takes into account the nonlinear behavior of the concrete and rebar and the geometric nonlinearity through P-Δ effects. The results showed that some structural elements (columns and beams) had non-linear behavior to different degrees between the two models, with collapse occurring in some of the ground floor columns of the 14-storey model (A) in different load cases studied.